Religion, Society and State in Nepal - Pant, Dipak Raj (Occasional Papers in Sociology and Anthropology, 2008)
The PDF of this file is 1,456 kbytes in size and therefore will take a long time to download if you click on the PDF link below. If you would like the file to be sent to you by email, please send a request to info@nepjol.info. Please include the citation below in your request. DOI: 10.3126/opsa.v3i0.1075 Occasional Papers in Sociology and Anthropology Vol.3 1993 p.47-57